2007
DOI: 10.1093/pasj/59.6.1107
|View full text |Cite
|
Sign up to set email alerts
|

Astrometry of H$_2$O Masers in Nearby Star-Forming Regions with VERA I. IRAS 16293$-$2422 in $\rho$ Oph East

Abstract: We report on results of multi-epoch VLBI observations of H$_2$O masers associated with a low-mass young stellar object, IRAS 16293$-$2422 in $\rho$ Oph East, and a fringe-phase and position reference source, ICRF J162546.8$-$252738, using the VLBI Exploration of Radio Astrometry (VERA) for high-precision astrometry. We obtained an annual parallax of a maser feature to be $\pi=$ 5.6$^{+1.5}_{-0.5}$ mas, corresponding to a distance of $D=178^{+18}_{-37}$ pc. We also found 10 relative proper motions of maser feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 19 publications
7
44
0
Order By: Relevance
“…This suggests that the eastern streamer is about 10 pc farther than the core, although more parallax measurements of sources in Lynds 1689 would be required to confirm this. Interestingly, Imai et al (2007) have measured the parallax of water masers in the protostar IRAS16293-2422, located in the northern part of Lynds 1689, and found a value ϖ= -+ 6.5 0.5 1.5 mas, which is consistent within 1 sigma with our parallax estimate for Lynds 1689 ( Figure 14). Notice that we have not considered SFAM 87 in the previous analysis.…”
Section: The Distance To Ophiuchussupporting
confidence: 84%
“…This suggests that the eastern streamer is about 10 pc farther than the core, although more parallax measurements of sources in Lynds 1689 would be required to confirm this. Interestingly, Imai et al (2007) have measured the parallax of water masers in the protostar IRAS16293-2422, located in the northern part of Lynds 1689, and found a value ϖ= -+ 6.5 0.5 1.5 mas, which is consistent within 1 sigma with our parallax estimate for Lynds 1689 ( Figure 14). Notice that we have not considered SFAM 87 in the previous analysis.…”
Section: The Distance To Ophiuchussupporting
confidence: 84%
“…We note that a second peak is seen between Aa and Ab, which could be associated with the A1 or A2β radio sources ). Identification of this structure is unclear, however, given that no other (sub)millimeter study found a corresponding detection toward these radio sources and that the radio emission in the region has complicated motions from different ejecta (e.g., Imai et al 2007;Pech et al 2010).…”
Section: Continuum Resultsmentioning
confidence: 98%
“…Water masers detections have also been reported toward source A through very long baseline (VLBI) observations (Imai et al 2007). The milliarcsecond resolution data revealed a spot exactly over Aa and another one to the SW of it (see Fig.…”
Section: H 2 O Masers and The Sio/co Outflowsmentioning
confidence: 93%